2022
DOI: 10.3389/fmed.2021.814908
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Stereopsis Using an Eye-Tracking Glasses-Free Display in Adults: A Pilot Study

Abstract: Purpose:To explore the feasibility and repeatability of a novel glasses-free display combined with random-dot stimulus and eye-tracking technology for screening stereopsis in adults.Methods:A total of 74 patients aged 18–44 years were recruited in this study (male: female, 32:42), including 33 patients with high myopia [≤ -6.0 diopters (D)] and 41 patients with moderate-to-low myopia (>-6.0 D). Stereopsis was measured using glasses-free, polarized, and Titmus stereotests. All patients completed a visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Several video-based infrared eye-tracking devices exist, but options for commercially available video recording systems suitable for binocularity assessment are scarce [ 21 , 22 ]. There are also very recent studies carried out with eye tracking, assessing ocular following responses in children [ 23 ] or other binocular vision and stereopsis tests [ 24 , 25 ]. Recent scientific evidence shows how eye tracker devices reduce the need for user interactions by directly and automatically measuring where the user is looking at.…”
Section: Introductionmentioning
confidence: 99%
“…Several video-based infrared eye-tracking devices exist, but options for commercially available video recording systems suitable for binocularity assessment are scarce [ 21 , 22 ]. There are also very recent studies carried out with eye tracking, assessing ocular following responses in children [ 23 ] or other binocular vision and stereopsis tests [ 24 , 25 ]. Recent scientific evidence shows how eye tracker devices reduce the need for user interactions by directly and automatically measuring where the user is looking at.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there have been several attempts at developing new computer-based stereoacuity tests. 2 , 8 16 However, studies have long since demonstrated that repeated testing with the same stimuli results in perceptual learning (i.e., improved perception of depth with an improvement in thresholds). 17 , 18 Some test-retest studies have found improvements in stereoacuity 19 , 20 despite a large interindividual variability.…”
Section: Introductionmentioning
confidence: 99%
“… 17 , 18 Some test-retest studies have found improvements in stereoacuity 19 , 20 despite a large interindividual variability. 3 , 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…Refractive error not only affects vision but also damages binocular visual function. In school-age children and adults, refractive error is the main cause of amblyopia [7]. Physiological refractive error usually has no symptoms.…”
Section: Introductionmentioning
confidence: 99%